Greening Program as a Green Campus Strategy to Support SDG 12 (Responsible, Consumption, and Production) and Foster Environmental Care Attitudes Among Undergraduate Biology Students - Mariska Elsya Anggraeni; Herlina Fitrihidajati; Adi Candra; Nurcholis; Aseyan (Indonesian Journal of Mathematics and Natural Science Education, 2026)
This study evaluates the effectiveness of a participatory greening program in implementing a Green Campus and achieving SDG 12 among Biology students. A quantitative pre-experimental, one-group pre-test post-test design was employed with 36 undergraduate student selected by purposive sampling. Instruments included expert-validated knowledge tests, environmental questionnaires, and observation checklist (content validity index of 1.00). The four-week program involved activities such as planting, watering, weeding, fertilizing, and monitoring, specially designed to promote sustainable consumption and production practice-including organic fertilization efficient water usage, composting, and responsible resources management. Student participation averaged 78.6%. Statistical analysis using the Wilcoxon signed-rank test indicated a significant increase in environmental knowledge (Z = -5.12, p < 0.001) with a moderate-to-high N-gain score of 0.66. Additionally, students’ environmental care attitude improved significantly, with the mean score rising from 72.4 to 88.7 (Δ = 16.3), categorized as “very positive”. These findings demonstrate that the greening program is empirically effective in improving ecological literacy and foresting pro-environmental attitude while reinforcing sustainable production principles. Therefore, this program can be adopted as a scalable and sustainable model for Green Campus initiative in higher education.